DWI FUNCTION MACHINE FOR PRODUCER OF PELET FISH USING SINGLE MOTOR - Rita Juliani; Friscylia Tampubolon; Sri Ratika Samosir; Mariana Simangunsong; Laurenchus Manurung (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
Has done machine fabrication dwi function printer pellets in the village Harean Porsea which aims to help fish farmers in producing pellets from rice straw waste. Methods used in starting from a design, provision of tools and material in continue with to prepare and pellet machine. The results machine dwi function printer pellets have been working maximally by the number of on average production pellets 6 kg per hour and machine dwi function having the engine propulsion that can serve as enumerators straw, smoothing keong mas and production pellets.